Searching for the origin of isoscaling: confinement and expansion - Dorso, Claudio Oscar (2011)
In this article the dynamical origin of isoscaling, the phenomenon first observed in heavy ion reactions, is explored by studying classical molecular dynamics simulations. Systems composed of neutron and proton-like particles and resembling a compound nucleus produced in heavy ion reactions are allowed to undergo a phase transition into clusters both while confined and during free expansion. Varying the isotopic number while maintaining the same atomic number, these simulations are used to obtain isoscaling fits of the ratio of fragment yields, and to elucidate the effect the dynamics of the reaction has on the isoscaling coefficients. It is observed that breakups at high density and before their final expansion are dominant in setting the values of the isoscaling coefficients α and β